Journalism's Relationship to Democracy: Roles, Attitudes, and Practices. (26th October 2019) - Wolfgang, J. David; Vos, Tim P.; Kelling, Kimberly
ABSTRACT: Journalism is often discussed in terms of its relationship to democracy. But one's conception of democracy can influence how one understands journalistic concepts. This study surveyed 204 US political reporters to determine their views on democracy and how their views relate to professional roles, trust, and sourcing. The findings show journalists support traditional norms but differ in their support in interesting ways based on their conception of democracy. Broadly, journalists more strongly support civic and direct models of democracy that highlight the interests of citizens. However, there is still notable support for pluralist and administrative models of democracy, which prioritize political interest groups and elite sources of information. Journalists, overall, might state support for a more citizen-focused and communitarian form of democracy, but there are continuing questions of how this might be reflected in the work of political journalists, specifically when these journalists are often highly dependent upon elite and official sources. This study explores the democratic ideals of journalists through those who cover politics and provides guidance for conceptualizing the relationship between journalism and democracy.